Social environment shapes female settlement decisions in a solitary carnivore. (18th October 2021) - Hansen, J E; Hertel, A G; Frank, S C; Kindberg, J; Zedrosser, A
Abstract: How and where a female selects an area to settle and breed is of central importance in dispersal and population ecology as it governs range expansion and gene flow. Social structure and organization have been shown to influence settlement decisions, but its importance in the settlement of large, solitary mammals is largely unknown. We investigate how the identity of overlapping conspecifics on the landscape, acquired during the maternal care period, influences the selection of settlement home ranges in a non-territorial, solitary mammal using location data of 56 female brown bears ( Ursus arctos ). We used a resource selection function to determine whether females' settlement behavior was influenced by the presence of their mother, related females, familiar females, and female population density. Hunting may remove mothers and result in socio-spatial changes before settlement. We compared overlap between settling females and their mother's concurrent or most recent home ranges to examine the settling female's response to the absence or presence of her mother on the landscape. We found that females selected settlement home ranges that overlapped their mother's home range, familiar females, that is, those they had previously overlapped with, and areas with higher density than their natal ranges. However, they did not select areas overlapping related females. We also found that when mothers were removed from the landscape, female offspring selected settlement home ranges with greater overlap of their mother's range, compared with mothers who were alive. Our results suggest that females are acquiring and using information about their social environment when making settlement decisions. Abstract : Information about the social environment may help female brown bears to select a settlement home range for breeding. We found that a female uses the identity of other females that overlapped her natal home range and female density when making settlement decisions. Specifically, females select settlement home ranges that overlap with home ranges of their mothers and familiar females known from their natal period. Relatedness does not appear to influence settlement decisions in this population.